Single and combined effect of acute sleep restriction and mental fatigue on basketball free-throw performance - Filipas, L.; Ferioli, D.; Banfi, G.; La Torre, A.; Vitale, J. A. (International Journal of Sports Physiology and Performance, 2021)
Purpose: This study aimed to investigate the single and combined effects of sleep restriction (SR) and mental fatigue (MF) on free-throw (FT) performance among adult male basketball players. Methods: A total of 19 amateur male basketball players performed, in a randomized, counterbalanced, and crossover order, 2 identical experimental sessions separated by an interval of 1 week. The difference between the 2 sessions was in the quantity of sleep the night before the sessions, as follows: in one case, the participants followed their habitual sleep-wake routines; in the other session, they were forced to sleep not more than 5 hours. During the experimental sessions, the participants performed 60 basketball FTs on 2 occasions, separated by watching a basketball tactical video for 30 minutes designed to induce MF. As such, the FT test was completed in 4 different conditions: control, MF, SR, and SR and MF combined. Results: The participants registered a significantly lower total sleep time in acute SR (P < .001). The subjective rating of MF was lower in the control than in MF, SR, and SR and MF combined (P < .001). There were no differences between conditions for the subjective ratings of motivation. FT accuracy was higher in the control than in MF, SR, and SR and MF combined (P = .010), while no differences were observed between the 3 experimental conditions (all P > .05). Conclusion: The results indicate that a combined effect of MF and SR induces a small reduction in basketball FT performance, similar to MF or SR alone.